Évaluation de l’activité antifongique des huiles essentiels de Laurus nobilis pour le traitement des onychomycoses - ADDOU, Hadjer; BECHLAGHEM, Samia (My University, 2024)
This study focuses on evaluating the antifungal activity of the essential oils of Laurus nobilis L. for the treatment of onychomycoses. Our work concentrated on valorizing a plant species that grows spontaneously in the coastal regions of Algeria, specifically Laurus nobilis L., by assessing the antimicrobial activity of its essential oils. The essential oils from the dry leaves of Laurus nobilis L. from the El-Hadjaj region (Mostaganem) were extracted by steam distillation, yielding 0.81%. Four fungal isolates (C1, C3, C5, and C6) provided by a research laboratory and other medical analysis laboratories were tested to verify the antimicrobial efficacy of the essential oils (EOs) of Laurus nobilis L. An aromatogram was performed using the solid medium diffusion method. This technique allowed us to quantitatively confirm the antimicrobial activity of the essential oils of Laurus nobilis L. on the studied isolates, followed by determining the minimum inhibitory concentration (MIC) and fungicidal concentration (MFC). The results of the aromatogram, the MIC, and MFC obtained from our experiments show that the fungal isolates are highly sensitive to the essential oils of Laurus nobilis L., with inhibition zones ranging between 34.40 and 60.95 mm in diameter and MIC and MFC values between 0.72 and 5.75 μl/ml successively.
Keywords: Laurus nobilis L.; Onychomycoses; Antimicrobial activity; Essential oils; Minimum inhibitory concentration.